Etnopedagogi Berbasis Kearifan Lokal Sasak untuk Mendukung Deep Learning dan Mindful Learning di Sekolah - Ahmad Turmuzi; Lalu Satria Siswandi; Masri Embat (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
This study examines ethnopedagogy as a link between in-depth learning and the application of Sasak cultural local wisdom in the context of school education. The focus of this study is traditional games such as selodor, gasing, jingklak, enjang-enjang, and dengklek, which are used as learning tools to create a fun, interactive, and meaningful learning process for students, without relying entirely on modern technology-based media. A qualitative literature study method was used to analyze various scientific journals, books, and previous studies that discuss in-depth learning, learning to think, ethnopedagogy, and Sasak culture. The research findings indicate that these Sasak folk games, which have been passed down through generations, are able to teach values ​​such as discipline, teamwork, concentration, self-awareness, emotional control, motor coordination, social interaction, and self-awareness. These games also support the pillars of mindful learning. Therefore, learning based on Sasak local wisdom can be an alternative in-depth learning method that still maintains local cultural identity